Hedgehog signaling pathway and ovarian cancer - Chen, Qi; Gao, Guolan; Luo, Shiwen (Chinese Journal of Cancer Research; Vol 25, No 3 (June 28, 2013): Chinese Journal of Cancer Research, 2013)
Epithelial ovarian carcinoma (EOC) is the most common form of ovarian malignancies and the most lethal gynecologic malignancy in the United States. To date, in spite of treatment to it with the extensive surgical debulking and chemotherapy, the prognosis of EOC remains dismal. Recently, it has become increasingly clear that in many instances, the signaling and molecular players that control development are the same, and when inappropriately regulated, drive tumorigenesis and cancer development. Here, we discuss the possible involvement of Hedgehog (Hh) pathway in the cellular regulation and development of cancer in the ovaries. Using the in vitro and in vivo assays developed has facilitated the dissection of the mechanisms behind Hh-driven ovarian cancers formation and growth. Based on recent studies, we propose that the inhibition of Hh signaling may interfere with spheroid-like structures in ovarian cancers. The components of the Hh signaling may provide novel drug targets, which could be explored as crucial combinatorial strategies for the treatment of ovarian cancers.